2011
DOI: 10.1016/j.intermet.2011.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Formation of the complete range of Ti5Si3−xGex solid solutions via mechanically induced self-sustained reactions

Abstract: a b s t r a c tThe complete range of Ti 5 Si 3 eTi 5 Ge 3 solid solutions was synthesised from elemental mixtures of Ti, Si, and Ge under an inert atmosphere via mechanically induced self-sustaining reactions (MSR). The stoichiometry of Ti 5 Si 3Àx Ge x solid solutions was controlled by adjusting the Si/Ge ratio of the initial mixture. The chemical composition and lattice parameters of the materials confirmed that Ti 5 Si 3 eTi 5 Ge 3 solid solutions with good chemical homogeneity could be produced via MSR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…A mechanically induced self-sustaining reaction (MSR) has been proven to be an attractive and affordable alternative to the conventional methods for producing advanced ceramics [7][8][9], ceramic matrix composites [10][11][12], ceramic-metal composites [13][14][15] and intermetallic compounds [16][17][18]. An MSR is a simple and low-energy-cost procedure that produces fine and homogeneous powders.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A mechanically induced self-sustaining reaction (MSR) has been proven to be an attractive and affordable alternative to the conventional methods for producing advanced ceramics [7][8][9], ceramic matrix composites [10][11][12], ceramic-metal composites [13][14][15] and intermetallic compounds [16][17][18]. An MSR is a simple and low-energy-cost procedure that produces fine and homogeneous powders.…”
Section: Introductionmentioning
confidence: 99%
“…This method, similar to selfpropagating high-temperature synthesis (SHS) [19,20], uses the strong exothermic character of the reactant powder mixtures to promote self-sustaining reactions induced by the mechanical energy supplied by high-energy ball mills [21]. It has been shown that the MSR technique allows obtaining complex solid solutions in a consistent and direct manner, with a high control of the chemical composition and microstructure [12,16,22].…”
Section: Introductionmentioning
confidence: 99%